Human adipose tissue‐derived stromal cells can differentiate into megakaryocytes and platelets by secreting endogenous thrombopoietin. (5th May 2016) - Ono‐Uruga, Y.; Tozawa, K.; Horiuchi, T.; Murata, M.; Okamoto, S.; Ikeda, Y.; Suda, T.; Matsubara, Y.
Abstract : Essentials Manufacturing platelets from a donor‐independent source is highlighted in transfusion medicine. We examined the differentiation of adipose tissue‐derived stromal cells (ASCs) into platelets. Endogenous thrombopoietin (TPO) induced ASCs differentiation into megakaryocytes and platelets. TPO secretion from ASCs was due to an interaction of transferrin with its receptor CD71. Summary: Background: Ex vivo production of megakaryocytes (MKs) and platelets from a donor‐independent source is currently of intense interest in transfusion medicine. Adipose tissue‐derived stromal cells (ASCs) constitute an attractive candidate cell source, because inducing these cells into MK lineages requires no gene transfer and only endogenous transcription factors containing p45NF‐E2/Maf, an MK‐inducing factor. Objectives: To examine whether ASCs differentiate into MK lineages by using endogenous thrombopoietin (TPO), a primary cytokine that drives MK lineages. Methods: TPO levels were measured by quantitative real‐time PCR and ELISA. To investigate the effects of endogenous TPO on MK and platelet production, surface marker expression and functions for platelets were analyzed in ASC‐derived cells cultured in the presence or absence of recombinant TPO. Based on a screening test, the role of transferrin receptor CD71 in TPO production and MK differentiation was examined with anti‐CD71 antibody, small interfering RNA (siRNA) against CD71 (siRNA‐CD71), and CD71‐positive/negative cells. Results: ASCs secreted TPO during MK differentiation, and the endogenous TPO facilitated MK and platelet production from ASCs. TPO secretion from ASCs occurred in a transferrin‐dependent manner. ASCs treated with anti‐CD71 antibody or transfected with siRNA‐CD71 produced markedly less TPO. The TPO levels and MK yield were significantly higher when CD71‐positive ASCs were used than when CD71‐negative ASCs were used. Conclusions: CD71 might be an appropriate marker for MK progenitor cells among human ASCs, because of the higher capacity of CD71‐positive cells to produce TPO and their ability to differentiate into MKs. These findings could help to establish an efficient method for platelet production.